2000
DOI: 10.1891/0047-2220.31.2.36
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Rehabilitation Services: Indicators of Successful Rehabilitation for Persons with Mental Retardation

Abstract: From its inception, the public vocational rehabilitation program has focused on efforts to assist Americans with physical and mental disabilities, through a variety of services, to become gainfully employed and self-reliant. This article describes a study in which the rehabilitation outcomes (i.e., closure status & weekly earnings) of persons with mental retardation were analyzed. Six predictor variables were used to predict one dichotomous and one continuous criterion variable: closure status and weekly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In other words, race and job placement appeared to positively affect closure success for persons with severe or profound mental retardation. These findings in part corroborate those from previous studies (Moore, 2001a;Moore et al, 2000) that identified job placement as a significant predictor of closure success for persons with mild and moderate mental retardation. Moore (2001a) reported that nearly 82% of VR consumers with mild and moderate mental retardation who received job placement services were successfully closed compared to approximately 51 % who did not receive such services.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, race and job placement appeared to positively affect closure success for persons with severe or profound mental retardation. These findings in part corroborate those from previous studies (Moore, 2001a;Moore et al, 2000) that identified job placement as a significant predictor of closure success for persons with mild and moderate mental retardation. Moore (2001a) reported that nearly 82% of VR consumers with mild and moderate mental retardation who received job placement services were successfully closed compared to approximately 51 % who did not receive such services.…”
Section: Discussionsupporting
confidence: 89%
“…The sine qua non of these studies has been that racial and ethnic members of underrepresented groups do not achieve rehabilitation success at the same rates as European Americans because such consumers are not provided with adequate VR services such as job placement and restoration. Although a few researchers (e.g., Moore, 2001a;Moore et al, 2000) have begun to focus their scientific inquiries on the VR outcomes of persons with mild and moderate mental retardation, the literature is void of applied empirical research regarding VR implications for persons who are African American and have severe or profound mental retardation. This study therefore examined the extent to which African Americans with severe or profound mental retardation achieve rehabilitation success in comparison to Caucasians with severe or profound mental retardation.…”
mentioning
confidence: 99%
“…, deaf non-Latinos(Moore, 2002a), consumers with mental retardation(Moore et al, 2000;Moore, Feist-Price, & Alston, 2002;Moore, Harley, & Gamble, 2004), deaf and hard of hearing consumers…”
mentioning
confidence: 99%
“…As agencies and counselors have traditionally been evaluated by number of successful closures, researchers have also frequently evaluated outcomes for state-federal VR consumers related to whether they achieved employment (e.g., Butterworth, Schalock, & Gilmore, 1998;Caston & Watson, 1990;Hill, 1989;Moore, Flowers, & Taylor, 2000;Schwab & DiNitto, 1993). Other authors have attempted to evaluate VR consumer outcomes beyond obtainment of employment at closure.…”
mentioning
confidence: 99%